2010
DOI: 10.5934/kjhe.2010.19.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Awareness and Practices for Diet according to Lifestyles of College Students

Abstract: The purpose of this study was to investigate the awareness and practices for diet according to the lifestyles of college students in Youngnam region. The data were collected by self-administered questionnaires during May 2007. One hundred-ninety samples were analyzed by SPSS Windows. Frequencies, Cronbach's alpha, factor analysis, cluster analysis, one-way analysis of variance, Duncan's multiple range test and chi-square test were conducted. The results were as follows. Lifestyles were categorized into four fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…이처럼 다이어트에 대한 사람들의 관심과 함께 다이 어트 관련 산업이 크게 성장함에 따라 다이어트는 개인의 욕구일 뿐만 아니라 문화적 트렌드로 자리 잡았다(Kwak과 Jung, 2015). 이에 따라 다이어트 관련 연구도 활발히 진행 되어 다이어트 의도 (Oh, 2015(Oh, , 2016, 다이어트 식품 구매 섭취 행동 (Ha 등, 2009;Han, 2017;Seong과 Pae, 2022), 다이어트 식습관 (Kim과 Sim, 2018;Lee 등, 2012;Seong 과 Pae, 2022), 다이어트 인식(Kim과 Kim, 2010;Kim 등, 2020;Oh, 2022a;Park, 2016), 다이어트 만족도(Kim과 Lee, 2006), 다이어트 행동실태 (Choi와 Ro, 2010;Doo와 Kim, 2008;Kim과 Yeon, 2017)…”
Section: 서 론unclassified
“…이처럼 다이어트에 대한 사람들의 관심과 함께 다이 어트 관련 산업이 크게 성장함에 따라 다이어트는 개인의 욕구일 뿐만 아니라 문화적 트렌드로 자리 잡았다(Kwak과 Jung, 2015). 이에 따라 다이어트 관련 연구도 활발히 진행 되어 다이어트 의도 (Oh, 2015(Oh, , 2016, 다이어트 식품 구매 섭취 행동 (Ha 등, 2009;Han, 2017;Seong과 Pae, 2022), 다이어트 식습관 (Kim과 Sim, 2018;Lee 등, 2012;Seong 과 Pae, 2022), 다이어트 인식(Kim과 Kim, 2010;Kim 등, 2020;Oh, 2022a;Park, 2016), 다이어트 만족도(Kim과 Lee, 2006), 다이어트 행동실태 (Choi와 Ro, 2010;Doo와 Kim, 2008;Kim과 Yeon, 2017)…”
Section: 서 론unclassified
“…Obesity, which arises from an imbalance of energy intake and expenditure, has a tremendous socioeconomic impact at an epidemic level. The World Health Organization (WHO) reported that two billion people suffer from obesity [ 1 , 2 ]. Obesity causes numerous complications such as hypertension, gallbladder disease, cardiovascular disease, heart failure, coronary artery disease, and stroke [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, obesity has become the 5th leading cause of death. The World Health Organization (WHO) reported that 2 billion people suffer from obesity and the global obesity population has doubled in the past two decades . Obesity causes numerous complications such as strokes, hypertension, gallbladder disease, cardiovascular disease, kidney cancer, and serious social problems .…”
Section: Introductionmentioning
confidence: 99%